P-71 How can we be research active? 'spotlight on practice' to showcase audit and service evaluation. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Short, Jill; Lipscombe, Erika; Morey, PJ
Abstract : Audit and evaluation has been a cornerstone of research activity at the Rowans Hospice since opening in 1994. In 2007 following a review of its audit monitoring structure, the Clinical Quality Strategy Group (CQSG) was developed to lead, coordinate and direct all clinical quality assurance activity. A key task for the CQSG was to ensure that audit results, outcomes, feedback and proposed new ways of working were actioned, as communication of these outcomes had been identified as minimally effective in changing practice. The CQSG implemented three actions aimed at improving the communication of project outcomes across the hospice: Action 1: An audit template with associated guide designed to help staff members develop robust proposals. Action 2: A requirement for staff to discuss proposal ideas with their line manager and a member of the CQSG to ensure work planned fits with the clinical strategy of the hospice. Action 3: The initiation of an 'executive summary' document aimed at facilitating a rigorous evaluation of the completed project and readable message/s for dissemination across the clinical teams. Rather than stopping there, to consolidate communication and dissemination of audit outcomes an in-house conference (Clinical Showcase): Spotlight on Practice was created in 2009, this is now an annual event. The conference showcases completed and ongoing service evaluations, audits or research projects to hospice staff, volunteers and trustees, and invited commissioners. The posters are displayed for a month, and the conference includes oral presentations and the award of prizes for best posters in specified categories. In this way outcomes are visible and both confidence and interest in involvement generated.